The Impact of Video-Mediated Communication on Closed Wound Assessments in Postoperative Consultations: Conversation Analytical Study - Stommel, Wyke J P; van Goor, Harry; Stommel, Martijn W J (JMIR Publications, 2020)
BackgroundResearch on the use of video-mediated technology for medical consultations is increasing rapidly. Most research in this area is based on questionnaires and focuses on long-term conditions. The few studies that have focused on physical examinations in video consultations indicated that it poses challenges for the participants. The specific activity of wound assessment through video in postsurgery consultations has not yet been studied. Furthermore, a comparative analysis of face-to-face and video settings on the moment-to-moment organization of such an activity is original. ObjectiveThe aim of this study was to examine the impact of video technology on the procedure of postsurgery wound assessment and its limits. MethodsWe recorded 22 postoperative video consultations and 17 postoperative face-to-face consultations. The primary purpose of the consultation was to inform the patient about the final pathology results of the resected specimen, and the secondary purpose was to check on the patient's recovery, including an assessment of the closed wound. The recordings were transcribed in detail and analyzed using methods of conversation analysis. ResultsThe way that an assessment of the wound is established in video consultations differs from the procedure in face-to-face consultations. In the consultation room, wound assessments overwhelmingly (n=15/17) involve wound showings in the context of surgeons reporting their observations formatted with evidentials ("looks neat") and subsequently assessing what these observations imply or what could be concluded from them. In contrast, wound assessments in video consultations do not tend to involve showing the wound (n=3/22) and, given the technological restrictions, do not involve palpation. Rather, the surgeon invites the patient to assess the wound, which opens up a sequence of patient and physician assessments where diagnostic criteria such as redness or swollenness are made explicit. In contrast to observations in regular consultations, these assessments are characterized by epistemic markers of uncertainty ("I think," "sounds...good") and evidentials are absent. Even in cases of a potential wound problem, the surgeon may rely on questioning the patient rather than requesting a showing. ConclusionsThe impact of video technology on postoperative consultations is that a conclusive wound assessment is arrived at in a different way when compared to face-to-face consultations. In video consultations, physicians enquire and patients provide their own observations, which serve as the basis for the assessment. This means that, in video consultations, patients have a fundamentally different role. These talking-based assessments are effective unless, in cases of a potential problem, patient answers seem insufficient and a showing might be beneficial.